The Implementation of Peer Assessment and Students Responses in Language Teaching Method Class - Riana Eka Budiastusti; Muhimatul Ifadah; Siti Aimah (Universitas Muhammadiyah Semarang, 2016)
Abstract. Being professional language teacher is principally about how teacher could understand and use the language orally and written well. Besides, professional teacher must also provide good assessment for their students. This study aimed to (1) measure to what extent does the implementation of peer assessment in Language Teaching Method (LTM) subject improve students performance; (2) identify problems appear in the implementation of peer assessment; (3) elaborate students' response upon implementing peer assessment. This study employed descriptive experiment design conducted in the 6th semester of 14 students of English Department, Unimus. The result showed that students performance upon the implementation of peer assessment in LTM subject increased significantly. There were several things to be underlined in this study, such as the high subjectivity in the process of assessing and the tendency of their unwillingness to be criticized. Therefore, generally students are encouraged and enthusiast in the learning process.